2002
DOI: 10.1002/etc.5620211014
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organochlorine residues and their bioaccumulation profiles in resident and migratory birds from North Vietnam

Abstract: Concentrations of persistent organochlorines (OCs), such as polychlorinated biphenyls (PCBs), 1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane (DDT) and its metabolites (DDTs), hexachlorocyclohexane isomers (HCHs), hexachlorobenzene (HCB), and chlordane compounds (CHLs), were determined in whole-body homogenates of resident and migratory birds collected from the Red River estuary, North Vietnam, during March and October 1997. Contamination pattern was in the order of DDTs > PCBs > HCHs > CHLs > HCB in both reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 44 publications
(70 reference statements)
3
9
2
Order By: Relevance
“…HCHs in white-breasted waterhen and slaty-breasted rail in this study exhibited similar levels to their kindred (1.5-2.0 ng/g ww for slatybreasted rail and 0.39-12 ng/g ww for white-breasted waterhen) found in North Vietnam (Minh et al 2002).…”
Section: Occurrence and Levelssupporting
confidence: 76%
“…HCHs in white-breasted waterhen and slaty-breasted rail in this study exhibited similar levels to their kindred (1.5-2.0 ng/g ww for slatybreasted rail and 0.39-12 ng/g ww for white-breasted waterhen) found in North Vietnam (Minh et al 2002).…”
Section: Occurrence and Levelssupporting
confidence: 76%
“…In addition, release from electrical equipment, leakages of hydraulic fluids from shipping vessels and old transformers and capacitors could be potential reason for elevated PCBs contamination encountered in mussels from coastal waters of these countries (Ramu et al 2007). Using resident and migratory birds as bioindicators, high concentrations of organochlorine insecticides and PCBs were found in birds collected at stopover/wintering areas of tropical Asian developing countries and Russia/Japan, respectively (Kunisue et al 2002aMinh et al 2002). To substantiate our findings with further evidence on pollution sources of organochlorines, we collected human breast milk from Asian countries and determined residue levels of contaminants ( Table 1).…”
Section: Status Of Contamination and Distributionsupporting
confidence: 64%
“…In Vietnam, higher levels of DDTs in sediments from densely populated areas as compared to those from paddy field were reported, indicating recent application of DDTs for public health purposes such as malaria control rather than for agriculture (Nhan et al 2001). In addition, our previous studies also demonstrated the elevated residue levels of DDTs in wild avian species (750-13,000 ng/g lipid wt) and foodstuffs (3.7-5,900 ng/g lipid wt) from Vietnam (Kannan et al 1997;Kunisue et al 2003;Minh et al 2002). Although fewer comprehensive investigations on POP pollution in Cambodia are available due to lack of monitoring of such pollutants because of long-term civil war, available studies reported that DDT has been used to control parasites of fish in cage culture (Tana 1996) and relatively high residue levels of DDTs were observed in fish (8-2,000 ng/g lipid wt) (Monirith et al 1999).…”
Section: Human Exposure and Human Health Implicationsmentioning
confidence: 87%
“…Interestingly, a study on pesticides concentration in wildlife in 1997 revealed that the concentration of DDT in the migratory birds is lower than in the resident ones in Vietnam (Minh et al, 2002). In particular, a relationships exist between places with elevated DDT and rate of exposure to DDT in resident birds from North Vietnam.…”
Section: Pesticides Environmental Burden: the North And The Southmentioning
confidence: 99%